2005
DOI: 10.1111/j.1540-8159.2005.09553.x
|View full text |Cite
|
Sign up to set email alerts
|

The Earliest Published Electrocardiogram Showing Ventricular Preexcitation

Abstract: When in 1930, Wolff, Parkinson, and White published what is today known as the WPW, or preexcitation syndrome, they, and subsequently others, found few comparable cases in the preceding literature. Among these the report of Cohn and Fraser, published in 1913, was the earliest. However, another even earlier documentation in a 1909 article by Hoffmann escaped notice till now. The ECG of a patient with paroxysmal tachycardia reveals a short PR interval and a delta-wave-induced widening of the QRS complex, even th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…However, in the present study, AD patients with the I/I genotype showed a rapid deterioration in neuropsychological assessments compared with those having other ACE genotypes. In addition, ACE I/D polymorphism is not a risk factor for vascular dementia and pathology . Therefore, we suggest that vascular pathology does not mediate the association between ACE I/D polymorphism and AD progression.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…However, in the present study, AD patients with the I/I genotype showed a rapid deterioration in neuropsychological assessments compared with those having other ACE genotypes. In addition, ACE I/D polymorphism is not a risk factor for vascular dementia and pathology . Therefore, we suggest that vascular pathology does not mediate the association between ACE I/D polymorphism and AD progression.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, ACE I/D polymorphism is not a risk factor for vascular dementia and pathology. 20,26 Therefore, we suggest that vascular pathology does not mediate the association between ACE I/D polymorphism and AD progression.…”
Section: Discussionmentioning
confidence: 79%
“…In dieser Publikation zitieren die Autoren einen Fallbericht von Frank Wilson von 1915 [ 47 ], der ein WPW-Syndrom erstmalig in der angloamerikanischen Literatur beschrieb. Von Knorre [ 43 ] hat sich die Mühe gemacht und nach dem ersten publizierten EKG eines WPW-Syndroms gesucht. Er konnte zeigen, dass bereits 1909 Hoffmann [ 15 ] ein EKG mit einem WPW-Muster publizierte.…”
Section: Die Ersten Beschreibungenunclassified